SPEECH CLASSIFICATION OF NATIONAL AND CULTURAL FEATURES OF PHRASEOLOGICAL UNITS OF THE GERMAN LANGUAGE (Scientific journal of the Fergana State University, 2024)
In the article, the speech expression of the national-cultural features of idioms in the German language and their classification in dictionaries were briefly studied and explained with the help of examples. By the last years of the 20th century and the beginning of the 21st century, various phraseological dictionaries in different languages ​​began to be published. These are the objectives set for themselves, the number of selected phraseological expressions, their composition, monolingualism or bilingualism, methods of placement of phrases and their interpretation, functional-stylistic description, polysemy, synonymy, antonymy, derivational features. prof. The interpretation of widely analyzed scientific and theoretical researches was used in Chapter II of M.E. Umarkhojayev's doctoral thesis entitled "Osnovi phrazeografii" entitled "Typologiya phrazeologicheskikh slovarey".